Differential kinetic profiles and metabolism of primaquine enantiomers by human hepatocytes. (December 2016) - Fasinu, Pius; Avula, Bharathi; Tekwani, Babu; Nanayakkara, N.; Wang, Yan-Hong; Bandara Herath, H.; McChesney, James; Reichard, Gregory; Marcsisin, Sean; Elsohly, Mahmoud; Khan, Shabana; Khan, Ikhlas; et al.
Abstract Background The clinical utility of primaquine (PQ), used as a racemic mixture of two enantiomers, is limited due to metabolism-linked hemolytic toxicity in individuals with genetic deficiency in glucose-6-phosphate dehydrogenase. The current study investigated differential metabolism of PQ enantiomers in light of the suggestions that toxicity and efficacy might be largely enantioselective. Methods Stable isotope13 C-labelled primaquine and its two enantiomers (+)-PQ, (−)-PQ were separately incubated with cryopreserved human hepatocytes. Time-tracked substrate depletion and metabolite production were monitored via UHPLC–MS/MS. Results The initial half-life of 217 and 65 min; elimination rate constants (λ) of 0.19 and 0.64 h−1 ; intrinsic clearance (Clint ) of 2.55 and 8.49 (µL/min)/million cells, which when up-scaled yielded Clint of 6.49 and 21.6 (mL/min)/kg body mass was obtained respectively for (+)- and (−)-PQ. The extrapolation of in vitro intrinsic clearance to in vivo human hepatic blood clearance, performed using the well-stirred liver model, showed that the rate of hepatic clearance of (+)-PQ was only 45 % that of (−)-PQ. Two major primary routes of metabolism were observed—oxidative deamination of the terminal amine and hydroxylations on the quinoline moiety of PQ. The major deaminated metabolite, carboxyprimaquine (CPQ) was preferentially generated from the (−)-PQ. Other deaminated metabolites including PQ terminal alcohol (m/z 261), a cyclized side chain derivative from the aldehyde (m/z 241), cyclized carboxylic acid derivative (m/z 257), a quinone-imine product of hydroxylated CPQ (m/z 289), CPQ glucuronide (m/z 451) and the glucuronide of PQ alcohol (m/z 437) were all preferentially generated from the (−)-PQ. The major quinoline oxidation product (m/z 274) was preferentially generated from (+)-PQ. In addition to the products of the two metabolic pathways, two other major metabolites were observed: a prominent glycosylated conjugate of PQ on the terminal amine (m/z 422), peaking by 30 min and preferentially generated by (+)-PQ; and the carbamoyl glucuronide of PQ (m/z 480) exclusively generated from (+)-PQ. Conclusion Metabolism of PQ showed enantioselectivity. These findings may provide important information in establishing clinical differences in PQ enantiomers.